Developmental regulation of lupulin gland-associated genes in aromatic and bitter hops (Humulus lupulus L.) - Josef Patzak (BMC, 2021)
Abstract Background Hop (Humulus lupulus L.) bitter acids are valuable metabolites for the brewing industry. They are biosynthesized and accumulate in glandular trichomes of the female inflorescence (hop cone). The content of alpha bitter acids, such as humulones, in hop cones can differentiate aromatic from bitter hop cultivars. These contents are subject to genetic and environmental control but significantly correlate with the number and size of glandular trichomes (lupulin glands). Results We evaluated the expression levels of 37 genes involved in bitter acid biosynthesis and morphological and developmental differentiation of glandular trichomes to identify key regulatory factors involved in bitter acid content differences. For bitter acid biosynthesis genes, upregulation of humulone synthase genes, which are important for the biosynthesis of alpha bitter acids in lupulin glands, could explain the higher accumulation of alpha bitter acids in bitter hops. Several transcription factors, including HlETC1, HlMYB61 and HlMYB5 from the MYB family, as well as HlGLABRA2, HlCYCB2–4, HlZFP8 and HlYABBY1, were also more highly expressed in the bitter hop cultivars; therefore, these factors may be important for the higher density of lupulin glands also seen in the bitter hop cultivars. Conclusions Gene expression analyses enabled us to investigate the differences between aromatic and bitter hops. This study confirmed that the bitter acid content in glandular trichomes (lupulin glands) is dependent on the last step of alpha bitter acid biosynthesis and glandular trichome density.